Assessment of active tectonics based on GIS and statistical model: A case study of upper Alaknanda catchment (western Himalaya, India) - Soumyajit Mukherjee; Mery Biswas; Adrija Raha (Bulletin of the Mineral Research and Exploration)
Due to continuing deformation of the Earth’s crust, degradation and aggradation processes, the upper part of the Alaknanda basin lying in the Garhwal Himalaya, India, is considered to be tectonically active. Active tectonics in this region made a considerable impact on the drainage system and the topographic expression. Using a digital elevation model (DEM) with a resolution of 30 m * 30 m and based on eight geomorphic indices [hypsometric integral (HI), drainage texture (Dt), asymmetry factor (AF), ruggedness number (Rd), circularity ratio (Rc), valley floor width/height ratio (Vfw), lemniscate coefficient (k) and basin shape index (Bs)], we evaluated active tectonics. Application of Index of Active Tectonic (IAT) and clustering model disclose the sub-watersheds in the southern part covering watersheds 16, 17 and near Badrinath sub-watershed 4, 9 and 8 are tectonically highly active (Class-1, 1.500-1.781). Cluster analysis defines two prominent clusters of sub-watersheds: 2, 4,14 and 15 in cluster 1; and 6, 7, 8 and 18 in cluster 2. Cluster 1 includes sub-watersheds 2, 4, 14, 15, and 16 and very high, high, and moderate IAT magnitudes. Sub-watersheds 6, 7, 8, and 18 are included in Cluster 2, which has very high and high tectonic activity